(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the dynamics of civilizational migration of poverty, theoretical-methodological foundations, systematic-functional analysis, future tasks and directions of the poverty reduction strategy. Also, the dynamics of civilizational migration of poverty and its specific features are philosophically analyzed.